Long-term stability of silica-composite sheet for smartphone-based colorimetric sensor in discrimination of airborne formaldehyde - Nhat-Truong Truong; Phuoc-Tri Mai; Minh-Kha Nguyen; Dung Van Nguyen; Long Quang Nguyen; Tuyet-Mai Tran-Thuy (Results in Engineering)
This study presents a type of silica-composite sensor fabricated by entrapping Nash reagent into a sol silica and ordered porous-silica mixture, integrated with a commercial polyester sheet, for the selective detection of airborne formaldehyde using smartphone-based colorimetry. After mild storage at 4 °C for up to 10 weeks, the as-fabricated silica-composite sensors remain durable performance in discrimination of airborne formaldehyde sensing within 10 min of exposure. The yellow coloration of 3,5-diacetyl-dihydrolutidine in the formaldehyde-exposed composite sensor could stabilize during two weeks of testing at 4 °C. Furthermore, the limit of detection and limit of quantification are 0.434 and 1.334 ppmv HCHO, respectively, achieved with Snolore approach. This achievement offers soft fabrication and storage conditions, along with portability, reliability and stable performance of the silica-composite sensor, addressing health concerns regarding indoor airborne formaldehyde through the development of ready-to-use detectors.